Effects of chemical reaction on MHD flow past an impulsively started infinite vertical plate with uniform heat and mass flux - Chandrakala, P. (Zielona Góra: Uniwersytet Zielonogórski)
Finite difference solutions of the unsteady MHD flow past an impulsively started infinite vertical plate with uniform heat and mass flux are presented here, taking into account the homogeneous chemical reaction of first order. The dimensionless governing equations are solved by an efficient, more accurate, unconditionally stable and fast converging implicit scheme. The effects of velocity, temperature and concentration for different parameters such as chemical reaction parameter, Schmidt number, Prandtl number, thermal Grashof number, mass Grashof number and time are studied.
Keywords: MHD; chemical reaction; vertical plate; heat flux; mass flux